2017
DOI: 10.1021/acsphotonics.7b00944
|View full text |Cite
|
Sign up to set email alerts
|

Generated Carrier Dynamics in V-Pit-Enhanced InGaN/GaN Light-Emitting Diode

Abstract: We investigate the effects of V-pits on the optical properties of a state-of-the art highly efficient, blue InGaN/GaN multi-quantum-well (MQW) light emitting diode (LED) with high internal quantum efficiency (IQE) of > 80%. The LED is structurally enhanced by incorporating pre-MQW InGaN strainrelief layer with low InN content and patterned sapphire substrate. For comparison, a conventional (unenhanced) InGaN/GaN MQW LED (with IQE of 46%) grown under similar conditions was subjected to the same measurements. Sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
46
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 72 publications
(50 citation statements)
references
References 46 publications
4
46
0
Order By: Relevance
“…As can be seen from the TRPL measurements, in the longer wavelength (500−510 nm) range (related peak with a dominant intensity is centered at 506 nm), the carrier PL lifetimes exhibit a slow mono-exponential decay. Based on the rate equation, this slower single exponential suggests high radiative recombination rate, which concurs with the high PL intensity and is in line with the results obtained in previous studies [29][30][31][32] . On the other hand, in the shorter wavelength (450−490 nm) range, the carrier lifetimes exhibit faster bi-exponential decay, due to the presence of multiple centers resulting from different states.…”
Section: Resultssupporting
confidence: 91%
“…As can be seen from the TRPL measurements, in the longer wavelength (500−510 nm) range (related peak with a dominant intensity is centered at 506 nm), the carrier PL lifetimes exhibit a slow mono-exponential decay. Based on the rate equation, this slower single exponential suggests high radiative recombination rate, which concurs with the high PL intensity and is in line with the results obtained in previous studies [29][30][31][32] . On the other hand, in the shorter wavelength (450−490 nm) range, the carrier lifetimes exhibit faster bi-exponential decay, due to the presence of multiple centers resulting from different states.…”
Section: Resultssupporting
confidence: 91%
“…The carrier dynamics of CsPbI 3 and CsPbBr 3 samples were investigated using time-resolved photoluminescence (TRPL) measurements to further confirm our findings and better understand the optical phenomena observed in Figure 3c,d (Table S1 in the Supporting Information shows the RT TRPL parameters). The total decay lifetime was fitted with bi-exponential decay functions (comprising both fast and slow decay components) due to the presence of multiple recombination centers, [51,52] as shown in Table S1. TRPL results indicated that the total lifetime was dominated by the slow decay component, which is indicative of highquality materials.…”
Section: Advanced Optical Analysis and The Band Structurementioning
confidence: 99%
“…To understand such carrier lifetime behavior in both materials, radiative and non-radiative components were analyzed, [51,54,55] and the results are reported in Figure 3e,f. As shown in Figure 3d, the lifetime of CsPbBr 3 at RT was dominated by radiative recombination (as it is in the same ns range of the total lifetime).…”
Section: Advanced Optical Analysis and The Band Structurementioning
confidence: 99%
“…No defect yellow luminescence (YL) band is observed, indicating superior crystal quality. 23,26 The RT PL emission spectrum of MAPI lm is shown in Fig. 1d.…”
Section: Resultsmentioning
confidence: 99%